2019
DOI: 10.1007/s00520-019-05114-3
|View full text |Cite
|
Sign up to set email alerts
|

Engaging hematopoietic cell transplantation patients and caregivers in the design of print and mobile application individualized survivorship care plan tools

Abstract: Purpose-INSPIRE (INteractive Survivorship Program with Information and REsources) is an online health program that includes a mobile app, website, health action plan, and individualized survivorship care plans for adult hematopoietic cell transplant (HCT) survivors. The INSPIRE program integrates two previously effective randomized control trials that tested an internet-based program and patient-centered survivorship care plans for HCT survivors. Methods-Three focus groups were conducted with a total of 22 par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
2
0
3
Order By: Relevance
“…(45,45%), são do ano de 2020 13,14,[16][17][18] , seguido do ano de 2021 com 2 (18,18%) das publicações 15,19 18,20 .…”
Section: Resultsunclassified
See 2 more Smart Citations
“…(45,45%), são do ano de 2020 13,14,[16][17][18] , seguido do ano de 2021 com 2 (18,18%) das publicações 15,19 18,20 .…”
Section: Resultsunclassified
“…a grande maioria, 9 (81,81%), é proveniente do Estados Unidos13,14,16,[18][19][20][21][22][23] . Isto se dá muito provavelmente pelo fato, já conhecido e…”
unclassified
See 1 more Smart Citation
“…Obtaining information is also achieved through educational interventions. [19][20][21][22][23][24][25][26] While there are a number of tools that may be harnessed to improve patients' understanding of their diagnosis and treatment, the use of such strategies should be patient-centered to ensure the type and amount of information provided by health care professionals addresses the needs and preferences of the patient. 15,[27][28][29] Clinical guidelines recommend that HSCT recipients are continually informed during the transplantation journey and encouraged to ask questions after the information session has been completed.…”
Section: Introductionmentioning
confidence: 99%
“…These include patient-clinician interaction, written/printed leaflets, audio-visual materials, telephone helplines, and more recently, websites accessed via the Internet. 1,[14][15][16][17] Recent reviews of randomized controlled clinical trials (RCTs) have evaluated the impact of information-giving interventions and demonstrated that in the main, these methods are effective, when enhancing understanding, knowledge and recall, and promoting satisfaction with communication. However, some information sources often are not tailored to the individual needs of cancer patients.…”
Section: Introductionmentioning
confidence: 99%